2017
DOI: 10.1259/bjr.20160059
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided radiotherapy for prostate cancer in the United Kingdom: a national survey

Abstract: Objective: To survey the technology and practice of image-guided radiotherapy (IGRT) for prostate cancer in the UK. Methods: A pre-tested semi-structured online questionnaire was sent to National Health Service (NHS) and private radiotherapy providers in the UK between March and April 2014. The survey was carried out on the Opinio© online platform. Results: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…So far, clinical implementations of MR-only radiotherapy for prostate cancer have used implanted fiducial markers for image guidance with the markers digitally added to the sCT [7] , [4] , [5] . However a significant number of centres do not use fiducial markers and employ CBCT soft-tissue matching for prostate radiotherapy treatments ( of UK centres) [8] . Additionally, radiotherapy treatments of many other cancers are not conventionally performed with implanted fiducial markers.…”
Section: Introductionmentioning
confidence: 99%
“…So far, clinical implementations of MR-only radiotherapy for prostate cancer have used implanted fiducial markers for image guidance with the markers digitally added to the sCT [7] , [4] , [5] . However a significant number of centres do not use fiducial markers and employ CBCT soft-tissue matching for prostate radiotherapy treatments ( of UK centres) [8] . Additionally, radiotherapy treatments of many other cancers are not conventionally performed with implanted fiducial markers.…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective studies have demonstrated IGRT can reduce late GU and GI toxicity (26)(27)(28). However, it is likely most men received IGRT in this cohort as a snapshot UK survey showed two-thirds of centres were using IGRT in March 2014, with this number likely to have increased over time (29). Furthermore, one would not expect there to be a significant difference in the use of IGRT across the H-RT and C-RT groups in the IMRT era.…”
Section: Strengths and Limitationsmentioning
confidence: 90%
“…A volumetric image with high spatial resolution and sufficient soft-tissue contrast is reconstructed and registered to the reference planning CT to determine the correct target position. Translational and rotational positioning errors can be corrected online before irradiation [ 23 , 24 , 101 103 ].…”
Section: Technological Advancesmentioning
confidence: 99%
“…At present, the precise identification of target volumes for treatment planning is mainly based on the integration of radiological/metabolic imaging, such as magnetic resonance imaging (MRI) or positron emission tomography (PET), with computed tomography (CT) scan simulation [ 15 20 ]. Tumour localisation immediately before and during treatment delivery by means of image-guided techniques is becoming a part of clinical practice and is a fundamental prerequisite for high-precision RT [ 21 24 ]. As part of a comprehensive RT treatment process, adaptive RT (ART) techniques make it possible to modify the treatment plan during the course of RT in order to account for anatomical and biological changes [ 13 , 25 ].…”
Section: Introductionmentioning
confidence: 99%